2012
DOI: 10.6026/97320630008430
|View full text |Cite
|
Sign up to set email alerts
|

Identification and classification of detoxification enzymes from Culex quinquefasciatus (Diptera: Culicidae)

Abstract: Molecular characterization of the insecticide resistance has become a hot research topic ever since the first disease transmitting arthropod (Anopheles gambiae) genome sequence has unveiled in 2002. A recent publication of the Culex quinquefasciatus genome sequence has opened up new opportunities for molecular and comparative genomic analysis of multiple mosquito genomes to characterize the insecticide resistance. Here, we utilized a whole genome sequence of Cx. quinquefasciatus to identify putatively active m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…This microarray study also identified that four other detoxification genes (three glutathione S-transferases (GSTs) and one esterase) were also over-transcribed compared to TPRI, although they were not differently expressed between Tororo resistant and sympatric unexposed controls. High expression of these genes alone or in combination with other detoxification enzymes could also be a possible mechanism associated with the bendiocarb phenotype as reported previously 76,77 , although in our data no significant synergist effect by DEM, a GST inhibitor, was observed. Further characterization of these genes is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…This microarray study also identified that four other detoxification genes (three glutathione S-transferases (GSTs) and one esterase) were also over-transcribed compared to TPRI, although they were not differently expressed between Tororo resistant and sympatric unexposed controls. High expression of these genes alone or in combination with other detoxification enzymes could also be a possible mechanism associated with the bendiocarb phenotype as reported previously 76,77 , although in our data no significant synergist effect by DEM, a GST inhibitor, was observed. Further characterization of these genes is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…Detoxification of synthetic or natural xenobiotics such as an insecticide or plant 86 toxins involves three phases consisting several metabolizing enzymes (Liska, 1998;87 Nakata et al, 2006;Reddy et al, 2012). Phase I mainly consists of the enzymes from 88 cytochrome P450 supergene family, where the P450 enzymes oxidize the parent molecule 89…”
Section: Introduction 49mentioning
confidence: 99%
“…sinensis , but there was no comparable gene in An. gambiae , Aedes aegypti or Culex quinquefasciatus . There are three genes in D. melanogaster , which represents a contraction of this subfamily in mosquito species.…”
Section: Resultsmentioning
confidence: 99%